2018
DOI: 10.14309/crj.2018.68
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Doppler Probe in the Diagnosis and Management of Upper Gastrointestinal Hemorrhage

Abstract: Through-the-scope (TTS) endoscopic Doppler ultrasound probe technology is a tool that has garnered interest for the evaluation of variceal and non-variceal bleeding. In previous studies, this technology has been proposed as a more objective method of identifying the bleeding subsurface blood vessel in peptic ulcer hemorrhage. We describe 3 cases where the use of an endoscopic Doppler probe guided the diagnosis and management of upper gastrointestinal (GI) hemorrhage due to causes other than peptic ulcer diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…There are two cases where EUS-guided coil/clip deployment combined with epinephrine injection was performed ( Table 7 ). In the case series of Satyavada et al , 22 EUS was used in the diagnosis and treatment of an obscure gastrointestinal bleeding which turned out due to Dieulafoy’s lesion. EUS-guided therapy was performed with the injection of 1:10,000 epinephrine and the deployment of four hemoclips.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are two cases where EUS-guided coil/clip deployment combined with epinephrine injection was performed ( Table 7 ). In the case series of Satyavada et al , 22 EUS was used in the diagnosis and treatment of an obscure gastrointestinal bleeding which turned out due to Dieulafoy’s lesion. EUS-guided therapy was performed with the injection of 1:10,000 epinephrine and the deployment of four hemoclips.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 20 articles were found, including 15 case reports and 5 case series. [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] The identifications of patients (including type of lesion, type of bleeding, and previous treatments), details of procedures (including specific type of treatment, type of needle), and main outcomes (including technical and clinical outcomes, and complications) for each study were reviewed. A total of 44 patients were induced and divided into different classifications according to the treatments.…”
Section: Methodsmentioning
confidence: 99%
“…While the former is treated per current guidelines, the latter is traditionally not treated endoscopically[ 43 ]. Preliminary studies have also demonstrated the use of doppler probe for the diagnosis and treatment of gastric varices, Dieulafoy’s lesion, diverticular bleeding, and post-ESD ulcers[ 45 ].…”
Section: Tts Doppler Probementioning
confidence: 99%